Constellations of Stains: The Matter of Experiencing and the Measure of Writing in the Essays by Józef Czapski and Marta Piwińska - Borowczyk, Jerzy (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2019)
This text is an attempt at repaying the author’s debt (both as an academic intellectual and as a regular reader) towards two inspiring essayists: Marta Piwińska and Józef Czapski. From the latter, the author of the article gained a lesson in establishing an intimate relationship with a work of literature he reads or a painting he views. From Piwińska he learnt the poetics of a mentally disciplined essay and gained the ability to associate the readings of the literature of the Polish Romanticism with contemporary sensitivity and the grand works of high modernism of the 20th century. In this article, the author analysed the records of fragments of the life and artistic struggles included in eight essays by Czapski (from the Patrząc and Czytając collections) as well as extensive essays with a literary studies’ focus by Piwińska (from books: Złe wychowanie and Juliusz Słowacki od duchów). The author focussed on the essayistic studies of the experiences of lostness and tiredness, the work of the mind, eyes and other senses, of spiritual and intellectual surprises, and even of moments of clairvoyance. He esteems the discussed essays particularly highly due to their exploratory value, which often takes the form of micro-stories, and elliptical and condensed biographical outlines. In these, readers are offered specific figures of artists and people engaged in everyday hustle and bustle. Both these groups encounter experiences which could be referred to as cornerstone lessons in existence.